Novel interstitial 2.6 Mb deletion on 9q21 associated with multiple congenital anomalies. Issue 1 (25th November 2013) - Pua, Heather H.; Krishnamurthi, Swetha; Farrell, Jessica; Margeta, Marta; Ursell, Philip C.; Powers, Martin; Slavotinek, Anne M.; Jeng, Linda J.B.
<x xml:space="preserve">Abstract</x> Array comparative genomic hybridization (aCGH) is now commonly used to identify copy number changes in individuals with developmental delay, intellectual disabilities, autism spectrum disorders, and/or multiple congenital anomalies. We report on an infant with multiple congenital anomalies and a novel 2.6 Mb interstitial deletion within 9q21.32q21.33 detected by aCGH. Her clinical presentation included dysmorphic craniofacial features, cleft palate, atrial septal defect, bicornuate uterus, bilateral hip dislocation, hypotonia, and recurrent pneumonia. Parental aCGH studies were negative for copy loss in this region. To our knowledge, no similar deletions have been reported in available databases or published literature. This deletion encompasses 12 genes, and prediction algorithms as well as experimental data suggest that a subset is likely to be haploinsufficient. Included are a neurotrophin receptor (NKG2D), a gene implicated in cilia function (KIF27), an adaptor protein important for ubiquitin‐dependent protein quality control (UBQLN1), a gene important for transcription and signaling (HNRNPK), and a gene involved in maintaining genomic stability (RMI1). Identifying additional patients with similar copy losses and further study of these genes will contribute to a better understanding of the pathophysiology of multiple congenital anomalies. © 2013 Wiley Periodicals, Inc.